The Use of Literary Works in Languange Classrooms at Indonesian Islamic University: a Postmethod Perspective - Dedi - Irwansyah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Literary works have been widely believed to be meaningful resources of linguistic input, cultural input, and values that can be used to teach native language or foreign language. The exploration of such belief in the postmethod era and at particular context like Indonesian Islamic university is still under research. This research is aimed at describing the teachers’ and students’ beliefs, attitudes, preferences, and experiences concerning the use of literary works at language classrooms. The research was a case study involving 8 lecturers and 9 students from Ma’arif Islamic Institute NU of Metro, Muhammdiyah University of Metro, and State Islamic Institute of Metro. The research data were collected through semi-structured interview, analyzed qualitatively, and validated through member checking technique. The findings of the research show that all respondents believe that literature is a pleasurable resource to teach language skills, enhance cultural and intercultural understanding, and inculcate transcendental dimension. Literature could be flexibly used in the opening, instructional, and closing phases of a lesson delivery. Literary works from various traditions are basically welcome. Developing a literature-based learning materials is feasible when it promotes language skills and contains values related to Indonesian multicultural education.